Probability : - Kinney, John J. (John Wiley & Sons, 1997)
This book uses a modern and visual approach to probability. It covers such topics as reliability, acceptance sampling, linear regression, quality production and quality control. It shows readers how to focus on the meaning of the results by making use of a computer algebra system that relieves the computational aspects of algebra and calculus. It integrates applications of probability to a variety of fields.